THE CORRELATION BETWEEN PRONUNCIATION AND LISTENING ACHIEVEMENT OF ENGLISH EDUCATION STUDY PROGRAM STUDENTS OF TRIDINANTI UNIVERSITY - Hotmaida Tampubolon; Yuyun Hendrety (Universitas Tridinanti Palembang, 2020)
The objective of this study was to find out whether or not there was a significant correlation between pronunciation and listening achievement of English education study program students of Tridinanti University and how much pronunciation contributed to listening achievement of English study program students of Tridinanti University. In this study, the researchers used correlation analysis. The population of this study was all English education study program students of Tridinanti University. The researchers used purposive sampling, and the sample was 53 students taken from the 3rd, 5th, 7th, and 9th semester. Pronunciation and listening achievement tests were used as the instruments. The finding showed that the pearson correlation coefficient was 0,086. It means that p-value (0.539) was higher than 0.85 which indicated that there was very low correlation between pronunciation and listening achievement of English education study program students of Tridinanti University. The regression analysis revealed that the significance value (ρ) was 0.284. It was higher than alpha value (α) 0.05 which indicated that students’ pronunciation gave a positive contribution toward their listening achievement and the value of R Square was 0.022. It could be concluded that students’ pronunciation contributed as much as 2.2 % toward their listening achievement.Keywords: correlation, pronunciation, listening achievement.